(untitled) (Conference on English Language Teaching, 2024)
With the growing number of language learning applications available, learners face difficulty choosing the platform that best suits their needs. Two AI-based language learning applications that are popular among language learners are Duolingo and Memrise. Duolingo emphasizes gamification and grammar, while Memrise focuses on spaced repetition and vocabulary. However, a clear understanding of how these differences impact user experience and learning outcomes remains limited. This proposed research conducts a comparative analysis of these two platforms, focusing on the experiences of university students learning English. The study focuses on a systematic review investigating the two apps. By synthesizing research findings, this review aims to provide a comprehensive understanding of the strengths and weaknesses of Duolingo and Memrise for language learners. This knowledge can inform future research on language learning app design and guide users in selecting the platform that best suits their learning goals and preferences.